Hemophagocytic Syndrome Associated with Immune Reconstitution Inflammatory Syndrome in a Patient with AIDS Related Burkitt's Leukemia/Lymphoma. (27th May 2014) - Kanıtez, Metin; Kapmaz, Mahir; Alpay, Nilufer; Selcukbiricik, Fatih; Çağatay, Atahan; Diz-Küçükkaya, Reyhan
Abstract : Highly active antiretroviral therapy (HAART) has markedly decreased human immunodeficiency virus- (HIV-) related mortality and the incidence of opportunistic infections. The dramatic reduction in HIV-1 RNA and increase in CD4 lymphocyte count mean a recovery in immune function. This restoration in immune function may be associated with paradoxical deterioration in subclinical opportunistic infections in some patients, a condition called immune reconstitution inflammatory syndrome (IRIS). IRIS, a "paradoxical" inflammatory response to either previously treated or subclinical infections or noninfectious diseases, can manifest during the restoration phase of immunity hemophagocytic syndrome (HS) which is a very rare complication in patients with acquired immune deficiency syndrome (AIDS). We describe a case of hemophagocytic syndrome associated with IRIS in a patient with AIDS related Burkitt's leukemia/lymphoma (BL). IRIS was probably the cause of hemophagocytosis for our patient. Zoster infection may facilitate to IRIS. With the increasing number of people with HIV infection and the accompanying use of HAART, much more clinical manifestations of IRIS will be experienced especially in patients given high dose chemotherapy, just like in our case.